PENGARUH GOOD CORPORATE GOVERNANCE DAN KINERJA KEUANGAN TERHADAP FINANCIAL DISTRESS AKIBAT PANDEMI COVID-19 PADA PERUSAHAAN PROPERTIES DAN REAL ESTATE YANG TERDAFTAR DI BEI PADA TAHUN 2019-2022 - M. Rega, Ghozaly; Ni Wayan Yulianita Dewi (Vokasi : Jurnal Riset Akuntansi, 2024)
This research aims to determine the influence of Good Corporate Governance and Financial Performance on Financial Distress Due to the Covid-19 Pandemic in Property and Real Estate Companies Listed on the IDX in 2019-2022. This research is quantitative research using secondary data obtained from the official IDX website and also from the official websites of related companies and measured using a ratio scale. The population in this research is all Property and Real Estate Companies registered on the IDX in 2019-2022. The sampling technique in this research used a purposive sampling method. Using a sample of 20 Properties and Real Estate companies listed on the IDX in 2019-2022. Data analysis in this research used descriptive analysis, classical assumption testing, multiple linear regression analysis and hypothesis testing with the help of the SPSS version 25.0 program. The results of this research show that: (1) Institutional Ownership has no effect on Financial Distress, (2) Managerial Ownership has no effect on Financial Distress, (3) Current Ratio has a positive effect on Financial Distress, (4) Quick Ratio has a positive effect on Financial Distress, and (5) Total Asset Turnover has no effect on Financial Distress